Pengaruh Beban Kerja, Stres Kerja, Kompensasi Terhadap Kinerja Karyawan Di PT. Cita Intrans Selaras - Sirajul Ulum; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
AbstractHuman resources are an important component in the continuity of the company so it is necessary to conduct research related to employee performance. In this study, employee performance is influenced by workload, work stress and compensation, so this research was conducted to determine the effect of workload, work stress and compensation on employee by performance the purpose of this research is to know that workload, work stress, and compensation have a (simultaneous) effect on employee performance and to know the individual (partial) effect of the independent variable on the dependent variable, namely the effect of workload on employee performance, work stress on employee performance, compensation on employee performance with quantitative research methods, associative approach, instrument test, classical assumption test, normality test, multiple linear regression analysis test, hypothesis test and R2 coefficient of determination testwith the results of the research showing that simultaneously there is a positive and significant influence simultaneously on employee performance, workload (X1) partially has a significant positive effect on employee performance, work stress (X2) partially has an insignificant positive effect on employee performance, compensation ( X3) partially has no significant negative effect on employee performancecompanies can maintain policies that are currently carried out, add variables or develop existing indicators in research. Keywords: workload, work stress, compensation and employee performance